IAI SPECIAL EDITION: Effect of Rosmarinus officinalis L inhalation on reducing primary dysmenorrhoea in female students of the Bali International University - Sutema, Ida Ayu Manik Partha; Mahardika, I Gede Argham (Pharmacy Education, 2022)
Background: Primary dysmenorrhea is a symptom that occurs in the absence of genital organ abnormalities. Non-steroidal anti-inflammatory drugs (NSAIDs) can be used but may cause adverse reactions if used repeatedly without doctor supervision. This study aims to analyse the effect of rosemary aromatherapy inhalation on reducing primary dysmenorrhoea in female students of the Bali International University. Method: This experimental research with a pretest and posttest control group design was conducted in March 2021 among 56 female students of the Bali International University. Pain intensity was measured by the Numerical Rating Scale (NRS) scale. Result: The Mann Whitney test revealed a p-value = 0.0001, indicating that rosemary aromatherapy (-3.250) has a significant effect on reducing the intensity of menstrual pain compared to jojoba oil used as a placebo (0,928). Conclusion: This research could demonstrate that rosemary aromatherapy inhalation can reduce pain levels and be a non-pharmacological therapy option for primary dysmenorrhoea.